The Royal Navy's new generation type 45 destroyer : acquisitions options and implications - Birkler, J. L., 1944-; Schank, John F. (John Frederic), 1946-; Arena, Mark V.; Smith, Giles K., 1928-; Lee, Gordon T., 1953-; Rand eBooks (Santa Monica, CA : RAND, 2002)
In the past decade, the Ministry of Defence (MOD) has become interested in evaluating a variety of different acquisition strategies that it might employ to acquire warships. It also has become increasingly aware of excess industrial capacity in the United Kingdom's warship-building sector. As a result, the MOD in 2001 asked RAND to help it (1) analyse the costs and benefits of alternative acquisition paths and (2) evaluate near- and long-term strategies that would yield the highest value, encourage innovation, use production capacity efficiently, and sustain the UK's core warship industrial base, given other current and future MOD ship programmes, with particular reference to the Type 45. The Type 45 is a new-generation destroyer that will become a main component in the Royal Navy's surface fleet, taking on roles as diverse as protecting the fleet in littoral settings, participating in hostile engagements on the open ocean, and conducting diplomatic and crisis-intervention missions. It will also constitute a large proportion of new-ship acquisitions that the MOD has planned for the next decades. RAND sought answers to three questions in its quantitative and qualitative evaluation: Should the MOD have the Type 45 built by one company or by two? Should the MOD compete the 12 ships in the Type 45 class, recognising that competition may result in a single producer, or should it directly allocate work to specific shipbuilders to ensure that both producers stay involved with the programme? Should the company or companies producing the Type 45 construct the destroyer in its entirety in one shipyard or assemble it from segments, or blocks, produced in several shipyards? The analysis results were a key input to the UK's decision to distribute the work on the ship, which will be made up of six blocks plus the superstructure, between two shipyards and assemble it at one of them. This book should be of special interest not only to the Defence Procurement Agency and to other parts of the Ministry of Defence, but also to service and defence agency managers and policymakers involved in weapon system acquisition on both sides of the Atlantic Ocean. It should also be of interest to shipbuilding industrial executives in the United Kingdom.
Introduction -- The Shipbuilding Industrial Base and the MOD Shipbuilding Programme -- Identifying and Analysing MOD's Acquisition Choices -- Analysis of Procurement Alternatives -- The Approved Type 45 Programme -- Issues Requiring Further Study -- Appendix A: Sensitivity Analysis -- Appendix B: Long-Term Implications of a Lack of Competition -- Appendix C: Building Ships in Blocks at Multiple Sites: Implications for the Type 45 Programme.
"RAND Europe."
Includes bibliographical references (p. 107-108).
Also available on the internet via WWW in PDF format.
Keywords: Great Britain. -- Royal Navy -- Procurement; Destroyers (Warships) -- Great Britain -- Design and construction; Electronic books